ANALISIS TERHADAP PENGATURAN DAN PENGAWASAN BANK DENGAN KELUARNYA UNDANG-UNDANG NOMOR 21 TAHUN 2011 TENTANG OTORITAS JASA KEUANGAN - EVAN TAMBUNAN; BISMAR NASUTION; MAHMUL SIREGAR (TRANSPARENCY, 2013)
The article of Law No. 3 of 2004 concerning to Bank Indonesia requires the establishment of supervision on financial service sector include banking, insurance, pension fund, security, venture capital and financing company an others institutions that manage the society fund. The institution with authority on regulation and supervision to financial service sector industries in Law No. 21 of 2011 is called as Financial Service Authority. The research method applied by writer is descriptive analytic study. The approach applied is normative juridical that review and test the data related to the issuance of Law No. 21 of 2011 concerning to OJK. The data is collected by library study to collect the secondary data. Based on the research, it is indicated that OJK has a positive and negative impact in banking. The positive impact is an effective coordination mechanism in handle any problems in financial system in order to assure the achievement of financial system stability and fulfill the supervision requirement such as independency, accountability, transparency, efficiency and affectivity of bank supervision. The negative impact is the obstacles in make coordination with the Bank Indonesia and any difficultness in apply the function of Central Bank as Lender of Resort because in the implementation of the function, central bank requires accurate and updated information about banking condition. The other impact may be occurred in the current financial condition and the high cost of banking supervision will cause the deficit of National Budget (APBN) Kata Kunci: OJK, Pengaturan dan Pengawasan Bank